Health and human rights education in U.S. schools of medicine and public health: current status and future challenges. - L Emily Cotter (Public Library of Science (PLoS), 2009)
Background Despite increasing recognition of the importance of human rights in the protection and promotion of health, formal human rights education has been lacking in schools of medicine and public health. Our objectives were: 1) to determine the nature and extent of health and human rights (HHR) education among schools of medicine (SOMs) and public health (SPHs); 2) to identify perceived barriers to implementing HHR curricula; 3) to learn about deans' interests and attitudes toward HHR education, and; 4) to identify factors associated with offering HHR education. Methods and principal findings We conducted a cross-sectional survey among deans of all accredited allopathic SOMs and SPHs in the United States and Puerto Rico. Seventy-one percent of U.S. SOMs and SPHs responded. Thirty-seven percent of respondents indicated that their schools offered some form of HHR education. Main barriers to offering HHR education included competition for time, lack of qualified instructors and lack of funding. Among schools not offering HHR education, 35% of deans were interested in offering HHR education. Seventy-six percent of all deans believed that it was very important or important to offer HHR education. Multiple regression analysis revealed that deans' attitudes were the most important factor associated with offering any HHR education. Conclusion Findings indicate that though a majority of deans of SOMs and SPHs believe that knowledge about human rights is important in health practice and support the inclusion of HHR studies in their schools, HHR education is lacking at most of their institutions. These results and the growing recognition of the critical interdependence between health and human rights indicate a need for SOMs and SPHs to work towards formal inclusion of HHR studies in their curricula, and that HHR competency requirements be considered to overcome barriers to its inclusion.